2002
DOI: 10.1128/aac.46.1.191-195.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activities of BMS-284756, a Novel Des-F(6)-Quinolone, against Staphylococcus aureus Strains with Topoisomerase Mutations

Abstract: The antistaphylococcal activities of BMS-284756 (T-3811ME), levofloxacin, moxifloxacin, and ciprofloxacin were compared against wild-type and grlA and grlA/gyrA mutant strains of Staphylococcus aureus. BMS-284756 was the most active quinolone tested, with MICs and minimal bactericidal concentrations against S. aureus wild-type strain MT5, grlA mutant MT5224c4, and grlA/gyrA mutant EN8 of 0.03 and 0.06, 0.125 and 0.125, and 4 and 4 g/ml, respectively. In the time-kill studies, BMS-284756 and levofloxacin exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Pharmacokinetic measurements with garenoxacin indicate that human serum drug concentrations will exceed this value for the entire dosing period (24 h) at the recommended 400-mg once-daily dosage (Fig. 2B), even if 75% of the agent is considered unavailable due to protein binding (11). We emphasize that the MPC has not been measured in vivo; determining whether concentrations that exceed the MPC measured in vitro are sufficient to block the development of resistance requires clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic measurements with garenoxacin indicate that human serum drug concentrations will exceed this value for the entire dosing period (24 h) at the recommended 400-mg once-daily dosage (Fig. 2B), even if 75% of the agent is considered unavailable due to protein binding (11). We emphasize that the MPC has not been measured in vivo; determining whether concentrations that exceed the MPC measured in vitro are sufficient to block the development of resistance requires clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the levofloxacin-resistant variants in the starting cultures revealed a variety of mutations in grlA/B. The S80Y, S80F, E84K, and A116P grlA mutations observed have been associated with phenotypic levofloxacin resistance in S. aureus (15,22,35), but the P144S grlA and the E422D grlB mutations do not appear to contribute to resistance (16,26,33). Other resistant subpopulations did not have mutations in the sequenced regions of grlA/B or gyrA/B.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have activity against a wide range of clinical isolates (1,7,12,34), and in particular, garenoxacin has been shown to have good activity against Staphylococcus aureus, both methicillin sensitive and resistant (6), and the respiratory pathogens Streptococcus pneumoniae (26), Haemophilus influenzae, and Moraxella catarrhalis (8). The activity of garenoxacin has been further assessed against strains of S. aureus with specific topoisomerase mutations (21), and more recently, it has been shown that garenoxacin has similar potency against both topoisomerase IV and gyrase (16) (dual-targeting quinolone), thus requiring mutations in both topoisomerases for resistance to occur (29). Although horizontal transfer is a major reason for the spread of ciprofloxacin-resistant strains, the role of antimicrobial selection may also play an important role.…”
mentioning
confidence: 99%